Eating behavior and cardiometabolic health : associations of eating habits with glucose and lipid metabolism in menopausal women - Kansanen, Mari (2021)
Background: Cardiovascular diseases (CVD) are the primary cause of death in women in developed countries. CVD risk increases with age and further accentuates after the onset of menopause in women. This finding suggests that menopause accelerates the progression of pathogenesis of CVD independent of chronological age. Eating habits also play an important role in the development of CVD. However, their role in attenuating the risk for CVD in menopausal women is not clear. The purpose of this thesis is to investigate the associations between eating habits and cardiometabolic risk factors in menopausal women.